Stimulating EFL Students' Motivation and Eagerness to Speak through an English Village - Pratiwi, Widya Rizky; Gusti, Herdie Idriawien; Acfira, Lukkyta Gusti; Khadijah Maming; Andriyansah, Andriyansah; Arifin, Andi Harmoko (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2023)
Most Indonesian researchers prove that learning English is considered difficult and tedious. However, the English Village differs from learning English in formal schools. English Village is designed as a place for students to learn English by directly practicing their speaking skills in an authentic environment and communicating with fun activities. English Village is held in collaboration with the Widyasatya Learning Centrum team, Bulukumba English Meeting Club, and Yayasan Pendidikan Umboh. This study was designed as a qualitative descriptive with a participant observation approach to describe the process of implementing English Village at PKBM Nadya, Kel. Ballasaraja, Kab. Bulukumba. 21 students and five instructors were involved in this activity. Data collection was observation and photos. Then the data is analyzed in six steps, from preparing raw data to drawing conclusions. This study found that English Village consists of fun activities; pre-test, self-introduction, sharing materials, art performance, games, discussion, gymnastic and outbound, and post-test. This English village enhances the students' cognitive and metacognitive domains that impact the improvement of students‘ motivation and eagerness to speak English. Therefore, this study promotes the English Village as an activity that can be used as a solution for teaching English in Indonesia. \]